The Untapped Power of Soda Taxes: Incentivizing Consumers, Generating Revenue, and Altering Corporate Behavior - Sarah A. Roache; Lawrence O. Gostin (Kerman University of Medical Sciences, 2017)
Globally, soda taxes are gaining momentum as powerful interventions to discourage sugar consumption and thereby reduce the growing burden of obesity and non-communicable diseases (NCDs). Evidence from early adopters including Mexico and Berkeley, California, confirms that soda taxes can disincentivize consumption through price increases and raise revenue to support government programs. The United Kingdom's new graduated levy on sweetened beverages is yielding yet another powerful impact: soda manufacturers are reformulating their beverages to significantly reduce the sugar content. Product reformulation - whether incentivized or mandatory - helps reduce overconsumption of sugars at the societal level, moving away from the long-standing notion of individual responsibility in favor of collective strategies to promote health. But as a matter of health equity, soda product reformulation should occur globally, especially in low- and middleincome countries (LMICs), which are increasingly targeted as emerging markets for soda and junk food and are disproportionately impacted by NCDs. As global momentum for sugar reduction increases, governments and public health advocates should harness the power of soda taxes to tackle the economic, social, and informational drivers of soda consumption, driving improvements in food environments and the public's health.